2021
DOI: 10.1042/ns20210036
|View full text |Cite
|
Sign up to set email alerts
|

Conventional protein kinase C in the brain: repurposing cancer drugs for neurodegenerative treatment?

Abstract: Protein Kinase C (PKC) isozymes are tightly regulated kinases that transduce a myriad of signals from receptor-mediated hydrolysis of membrane phospholipids. They play an important role in brain physiology, and dysregulation of PKC activity is associated with neurodegeneration. Gain-of-function mutations in PKCα are associated with Alzheimer’s disease and mutations in PKCγ cause spinocerebellar ataxia type 14. This article presents an overview of the role of the conventional PKCα and PKCγ in neurodegeneration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 116 publications
0
10
0
Order By: Relevance
“…For conventional PKC isozymes, loss-of-function somatic mutations or reduced protein levels are associated with cancer (3); in contrast, gain-of-function variants have been identified in neurodegenerative diseases (4)(5)(6). Thus, whereas reduced protein levels and activity of conventional PKC isozymes are associated with poorer patient survival in cancers such as colon and pancreatic cancer, enhanced activity of the conventional PKC is associated with Alzheimer's disease (4,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…For conventional PKC isozymes, loss-of-function somatic mutations or reduced protein levels are associated with cancer (3); in contrast, gain-of-function variants have been identified in neurodegenerative diseases (4)(5)(6). Thus, whereas reduced protein levels and activity of conventional PKC isozymes are associated with poorer patient survival in cancers such as colon and pancreatic cancer, enhanced activity of the conventional PKC is associated with Alzheimer's disease (4,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is the unbiased approaches that provide the most compelling evidence for the critical role of PKC in maintaining normal brain function. A comprehensive phosphoproteome analysis by Tagawa et al 29 revealed that PKC substrates account for over half of the core molecules that display increased phosphorylation in AD brains, a finding supported by subsequent phosphoproteomics studies identifying PKC as one of the main kinases activated in AD 30 , and reporting increased phosphorylation of PKCα at Thr638 60 , a quantitatively phosphorylated C-terminal site that serves as an indicator of PKC steady-state levels 61 , 62 . Gain-of-function variants in PKCα segregating with affected family members in LOAD first drew specific attention to this conventional PKC isozyme 21 .…”
Section: Discussionmentioning
confidence: 95%
“…Mounting evidence points to cancer-associated variants in PKC generally being loss-of-function and variants present in neurodegenerative disease having gain-of-function alterations (39, 64, 65). In this study, we show that mutation of a conserved residue in the C1A domain of cPKC leads to opposing phenotypes depending on the disease context.…”
Section: Discussionmentioning
confidence: 99%